Development of a hybrid power management unit for mobile applications: solar energy case study - Abdelmoaty, Ahmed (AUC Knowledge Fountain, 2013)
Applying photovoltaic power to mobile devices has become a hot area of research due to the availability of solar energy. Usage of photovoltaic as the power source for mobile devices will enhance device performance. There are many challenges to interface photovoltaic energy to mobile loads such as variation of power coming out from photovoltaic panels, unregulated voltage and limited power. Maximum power point tracking (MPPT) is used in photovoltaic systems to maximize the photovoltaic array output power under environmental variations such as irradiation and temperature for mobile applications. A power management system is proposed to apply photovoltaic harvested energy effectively to mobile or handheld devices while running workloads. The proposed system mainly consists of a MPPT block and a Power Distribution Control Unit (PDCU). The PDCU allows usage of an AC/DC external in case of insufficient photovoltaic power in order to maintain the load running. Different cases of operation are handled by the PDCU unit depending on the availability of photovoltaic power, load power, battery state of charge and existence of the AC/DC external. In addition, a new MPPT algorithm is proposed to provide fast and accurate tracking. Analysis and simulation results are provided to demonstrate system functionality and performance sensitivity. Moreover, a prototype of the proposed system is still under progress, to verify the possibility of building such system.